Measurement of Visitors’ Satisfaction towards Health Tourism: Structural Equation Modeling Analysis - Afzal Hossain (Health Economics and Management Review)
Health tourism is an emerging concept in the tourism industry. It is the act of traveling to obtain medical care. Health tourism is also a unique thought in the travel and tourism industry. A large number of people travel for treatment every year. Health tourism helps to develop the economy and living standards of human civilization. It is a market combination of the healthcare and tourism sectors. Health tourism is growing day by day internationally as well as nationally. When people travel to a foreign region to get medical treatment, many issues and challenges arise. Health tourism facilitators play a vital role in the travel and tourism sector. It also plays a significant role in making the medical travel easy and comfortable. In the country of destination, health tourism encourages economic development and raises the quality of healthcare provided. In many of these developing countries, health tourism represents a lucrative and growing source of economic revenue. Therefore, the purpose of this research was to use partial least square structural equation modeling (PLS-SEM) to measure the visitors’ satisfaction towards health tourism in the perspectives of Bangladesh. This research used both quantitative and descriptive analysis methods. A standardized questionnaire was used to collect data from a sample of 205 local visitors using a purposive sampling technique. A partial least square structural equation modeling (PLS-SEM) approach was used to measure the data and test the hypotheses. The results of the PLS-SEM analysis method revealed that product, place and process had a significant and positive impact on visitors’ satisfaction in the contexts of health tourism in Bangladesh. The results of the investigation can offer value insights for academicians to do future authorizations. It can be also helped for practitioners to design suitable marketing strategies for visitors’ satisfaction towards health tourism as a destination in Bangladesh.